Kinetic and thermodynamic assessment of the Potency of irvingia gabonensis plant extract as an Eco-friendly inhibitor for mild steel in an acidic Environment - Silas Oseme Okuma; Ejovi Okuma Ogagavwodia; Martins Obaseki; Cynthia Chinasa Nwaeju (European journal of materials science and engineering, 2023)
The kinetic and thermodynamic efficacy of Irvinga Gabonensis plant extract as an effectiveeco-friendly inhibitor for mild steel in acidic environment were studied using gravimetric measurement (GM) at varied temperature of 298,308, and 318 K, as well as scanning electron microscopy surface characterization, and were utilized. The findings indicate that Irvinga Gabonensis leaf extract inhibited acid-induced corrosion of MS effectively. The results of thekinetic analysis indicated that the inhibited species were more resilient. The extract's effectiveness as an inhibitor is determined by its concentration (C) and temperature (T). The active components of the extracts were found to adhere to the Langmuir adsorption isotherm, resulting in an adsorption-based inhibitory mechanism. It was also established from the study that the extract is a mixed-type inhibitor. SEM characterization further revealed that thesurfaces were devoid of pits when the extract is present.
Keywords: Thermodynamic; Kinetic; Mixed-Type inhibitor; Irvingia Gabonensis; Phytochemical